Le rôle du contrôle juridictionnel comme technique de participation - Henry, J. (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The use of the « costs-advantages balance » theory by the French Administrative Courts would appear to give them a far-reaching supervisory jurisdiction over administrative decisions. However, precedents concerning environmental consequences of proposed nuclear plants show that the Courts are ill-equipped to deal with such cases and apply the « costs-advantages » theory. Therefore, they are reticent to annul administrative decisions as ill-founded or unreasonable. The concept of abuse of power is also of little help since it is almost impossible for the Courts to substitute their own findings to the Administration's as to the public necessity of a project. In conclusion, the Administrative Court is not an appropriate forum and the system may only gives false hopes to ecologists and others who pursue changes in government energy orientations and decisions.